Analisis Persepsi Kemudahan Penggunaan, Kenyamanan, Manfaat Dan Kepercayaan Yang Mempengaruhi Minat Menggunakan Bsi Mobile Palopo - Megasari Megasari; Nila Kartika Putri (Al-Kharaj: Journal of Islamic Economic and Business, 2021)
This study aims to analyze the perceptions that determine customer interest in using BSI Mobile at Bank Syariah Indonesia. This type of research is a descriptive quantitative study with a population of all customers using BSI Mobile at BSI KCP Palopo Ratulangi with a sample of 201 respondents using the slovin formula. The data analysis technique used is multiple linear regression with hypothesis testing using the t test, F test and the coefficient of determination test (R2). The results of data analysis with the t test show that partially the variables perceived ease of use (X1), perceived convenience (X2), perceived benefits (X3) and perceived trust (X4) have a significant effect on customer interest (Y) using BSI Mobile at BSI KCP Palopo Ratulangi. This can be seen from the perceived ease of use (X1) with a tcount (4.947) > ttable (1.972) and a probability value of 0.000 <0.05; perceived comfort (X2) with a tcount (3.123) > ttable (1.972) and a probability value of 0.002 <0.05; perceived usefulness (X3) with a tcount (2.538) > ttable (1.972) and a probability value of 0.002 <0.05; and perceptions of trust with tcount (3,850) > ttable (1,972). The results of the F test also show that the four perception variables simultaneously influence customer interest in using BSI Mobile with a probability value of 0.000 <0.05. Meanwhile, the coefficient of determination (R2) of 0.479 indicates that 47.9% of variations in customer interest in using BSI Mobile can be explained by perceptions of ease of use, convenience, benefits and trust, while the remaining 52.1% is explained by other variables not examined in this study.